NARRATIVE ANALYSIS OF UNDERSTANDING AND USE OF DIGITAL WALLETS IN SOCIETY: LITERATURE STUDY - Ibrahim Hanif; Restu Nur Raida; Syafrinadina (Indragiri Research Center (ingreat), 2025)
Digital wallets have become a crucial part of Indonesia's financial transformation, with rapid user growth. However, public understanding of this technology remains uneven and faces data security challenges. This study aims to analyze narratives about digital wallet understanding and use through a literature review, focusing on factors influencing adoption and the security challenges faced. The research method employed a qualitative, descriptive-narrative approach through analysis of secondary sources. The results indicate that people adopt digital wallets primarily due to perceived convenience and efficiency, but in-depth understanding of security features remains low. The learning process occurs socially through community networks, with key figures such as youth acting as knowledge brokers. Communities develop hybrid adaptation strategies where digital systems are used alongside traditional financial practices according to the local context. In conclusion, understanding of digital wallets is a social construct shaped through the interaction of technology, culture, and community networks. Implications of this study emphasize the importance of contextualized digital literacy programs, increased transparency of platform security, and educational approaches that leverage natural social learning mechanisms within communities.